Librarianship and documentation: an international perspective, de Herbert Coblans - Nery da Fonseca, Edson (Revista de Biblioteconomia de Brasília, 1975)
COBLANS, Herbert. Librarianship and documentation: an international perspective. London: Andre Deutsch, 1974. 142 p. (Grafton basic texts).